Czytelnictwo w bibliotece technicznej –60 lat doświadczeń Biblioteki Głównej Politechniki łódzkiej (1945-2005) - Sójkowska, Iwona (Acta Universitatis Lodziensis. Folia Librorum, 2010)
The Library of the Technical University of Łódź was established in 1945. Library space conditions have improved significantly for the last 60 years. Subsequent reading rooms were organized, branch libraries were set up and finally, at the beginning of 21st century, the library moved to a new, separate, modern building. The library’s holdings have been developed in systematic way by supplementing and updating the collection of Polish and foreign literature. Positive relationships with users and friendly atmosphere have been always of the highest priority. Computer technology development has changed users attitude toward a library and added a new phenomenon to traditional readership – electronic publications usage. The article describes the way reading process, the library users and their reading habits have changed for the last 60 years. It also presents various types of cooperation with library users. Special attention is paid on professional literature readership and on different forms of documents usage.